Systemic therapies in patients with advanced well-differentiated pancreatic neuroendocrine tumors (PanNETs): When cytoreduction is the aim. A critical review with meta-analysis. (December 2018) - Pozzari, Marta; Maisonneuve, Patrick; Spada, Francesca; Berruti, Alfredo; Amoroso, Vito; Cella, Chiara Alessandra; Laffi, Alice; Pellicori, Stefania; Bertani, Emilio; Fazio, Nicola
Highlights: Cytoreductive role of systemic antitumor therapies in advanced PanNETs is unclear. Waterfall Plot gives a wider view of tumor shrinkage impact. Chemotherapy-based treatments seem to have a key-role in cytoreduction. Homogeneous PanNETs populations should be investigated in future clinical trials. No clear predictive factors emerged. Abstract: Introduction: Cytoreduction is sometimes an important aim of systemic anti-tumor therapies in well-differentiated pancreatic neuroendocrine tumors (PanNETs). As there is not a gold standard treatment for these tumors in this field, we conducted a literature review in order to identify objective criteria for treatment choice. Materials and methods: We critically reviewed and performed a meta-analysis of all published clinical studies of systemic therapies in patients with well-differentiated unresectable PanNETs, selecting only those articles which reported tumor shrinkage (TS) with a waterfall plot (WP). Tumor downsizing of ≥10% was considered as objective response. Results: We selected 17 out of 2758 studies, comprising 1118 patients with tumor response reported as WP. Proliferation index, tumor burden and anti-tumor therapies were heterogeneous. Chemotherapy alone (mainly, capecitabine/temozolomide) or in combination showed the best results, with ≥10% TS ranging from 65% to 93%. Peptide receptor radionuclide therapy combined with chemotherapy (Chemo-PRRT) and sunitinib appeared promising by inducing objective response in a significant proportion of patients (93% and 60%, respectively). Time to tumor response was reported in only two trials. No clear clinical and/or biological predictive factors emerged. Conclusion: Based on response criteria used in our retrospective analysis, systemic chemotherapy alone or in combination appeared to have the main cytoreductive impact. However no conclusions regarding either a specific regimen or combination can be drawn. Furthermore, tumor population selection and/or choice of regimen may have a significant influence. Further analysis should be also conducted to identify potential predictive biomarkers of responses, in order to design future prospective interventional clinical trials enrolling more homogenous populations of advanced well-differentiated PanNETs.